"If You're Gonna be Inclusive, You have to be Inclusive on all Levels": Ableism in Teacher Collaboration. Issue 3 (24th October 2021) - Phuong, Jennifer; DiPasquale, Katherine; Rivera, Natalie
Abstract: In this piece, we explore how ableism manifests in teacher collaboration, focusing on the experiences of English as a Second Language teachers and special education teachers. We broaden the definition of ableism to consider how schools rely on ideas of some students as normal and others as not, leading to a service delivery model. The service delivery model results in fragmented and compartmentalized views of students that see language and disability needs as distinct, thus leading to difficulties for the teachers who work with students who are labeled disabled and as English Learners. We end with reflection questions for administrators and educators to consider to better serve the needs of their students.